Evaluation of total phenolic content, antioxidant activities, caffeine, and chlorogenic acid content in single-origin green coffee beans grown in Thailand - Orpong, Piyanuch; Picha, Roppon; Chookaew, Sirilak; Eamsiri, Jaruratana; Sriwiang, Wiranee; Saengkorakot, Chakrit; Khemthong, Khemruji (Asia-Pacific Journal of Science and Technology, 2025)
Third-wave coffee culture has placed emphasis on the quality and origin of coffee beans. Chemical and physical properties as measured scientifically can augment sensory characteristics of single-origin coffee in identifying their geographical identities. This study aimed to assess the properties of 31 green coffee bean samples, comprising 23 Arabica and 8 Robusta species, collected from 12 Thai provinces. The total phenolic content, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) antioxidant activities, and concentrations of chlorogenic acid and caffeine were measured using the Folin-Ciocalteu method, DPPH and FRAP assays, and high-performance liquid chromatography (HPLC). The distributions of measured quantities and their correlations were examined by species and by origins. The results showed that the total phenolic content, antioxidant activity and caffeine concentration in Robusta species were significantly higher than in Arabica species. Additionally, chlorogenic acid content in Robusta was slightly higher than in Arabica but there was no significant difference between species. From the samples measured, Robusta coffee from Tak, Sisaket, Ranong, and Chumphon consistently ranked highest in terms of total phenolic content, FRAP, and DPPH values. For chlorogenic acid and caffeine contents, Chumphon Robusta and Phitsanulok Arabica samples ranked the highest. Overall, across species and regions, strong correlations were found among the five measured quantities as indicated in Pearson’s coefficients and principal component analysis. The data can be used as supplementary information to assess the differences and characteristics of green single-origin coffee beans from different parts of Thailand.